Synthesis and surface characterization of new triplex polymer of Ag(I) and mixture nucleosides: cytidine and 8-bromoguanosine - Lamia L.G. Al-mahamad (Heliyon, 2019)
In this work one-dimensional (1D) triplex polymer of silver (I): mixture nucleosides of cytidine and 8-bromoguanosine was synthesised. The polymer showed high stability due to the presence Ag(I) ions in the structure of the polymer in addition to the stability that produces from the effect of Hoogsteen hydrogen bonding in the triplex CGC. Atomic Force Microscopy (AFM) and transmission electron microscopy (TEM) were used to investigate the morphology of the polymer. The AFM images revealed formation of nanofibres extending many microns in length with height in the range of 2–3 nm. Statistical analyses carried out to analyse the AFM images to determine the height of the loops that formed in the polymer. The data displayed that the height value was in the range between 10 nm to 15 nm. The data of TEM images were consistent with the data of AFM images by displaying a very long fibre. Gwyddion software program was used to investigate surface parameters (roughness and waviness), diameter (size distribution), and probability density of the fibre. The data showed that the diameter of the fibre was ∼0.4 nm.